Spatial–Seasonal Mapping of Estuarine Bed Sediment Texture Under a Natural Mouth-Closure Regime: Evidence from the Kungkai Baru Estuary, Western Indonesia - Nofridiansyah, Eko; Hartoko, Agus; Muskananfola, Max Rudolf; Helmi, Muhammad; Adi, Wahyu (JFMR-Journal of Fisheries and Marine Research, 2026)
Seasonally closed estuaries are vulnerable coastal systems in which alternating phases of mouth closure and opening strongly influence hydrodynamics, sediment transport, and benthic habitats. The Kungkai Baru Estuary on the wave-dominated western coast of Sumatra, Indonesia, is a small tropical estuary that predictably closes during the west monsoon and re-opens during the east monsoon. Although previous studies have documented major morphodynamic changes and shifts in macrozoobenthic communities between these phases, the associated near-bed sediment dynamics remain insufficiently understood. This study examined spatial and seasonal patterns of bed sediment texture using surface sediment samples collected at 21 stations during closed-mouth and open-mouth conditions and analysed through grain-size distribution and Folk–Ward statistics. Bed sediments were overwhelmingly sandy (>96% sand), but mean grain-size, sorting, and skewness showed clear spatial and seasonal variation. During the closed-mouth season, moderately well-sorted fine to medium sands dominated the middle and upper estuary, indicating reduced marine energy and greater retention of finer material. During the open-mouth season, coarser and more poorly sorted sands occurred near the estuary entrance, reflecting stronger marine influence and more active sediment exchange. These findings align with previously reported longitudinal patterns in macrozoobenthos and provide a sediment-based framework for understanding benthic habitat heterogeneity in seasonally closed tropical estuaries.